Cloning and expression of xylitol dehydrogenase gene from Candida shehatae in Saccharomyces cerevisiae - Boonmee, Atcha (Asia-Pacific Journal of Science and Technology, 2017)
The inability of Saccharomyces cerevisiae to utilize xylose is attributed to its inability to convert xylose to xylulose. Low xylose reductase and xylitol dehydrogenase activities in S. cerevisiae are regarded as the reason of blocking the pathway from xylose to xylulose. In previous study, we cloned and expressed the xylose reductase gene from Candida shehatae in S. cerevisiae which enables it to grow in xylose-containing medium. In this study, we investigated the activity of xylitol dehydrogenase gene of C. shehatae in S. cerevisiae. The xylitol dehydrogenase gene (XYL2) from C. shehatae was amplified by polymerase chain reaction (PCR). It was placed into plasmid pSFAU to produce the recombinant expression vector pSFAU-XDH. Subsequently, the pSFAU-XDH vector was transformed into S. cerevisiae TISTR5339 to produce a recombinant S. cerevisiae TISTR5339-XDH. The recombinant S. cerevisiae showed higher growth rate than the untransformed strain in media containing xylitol as a carbon source. The specific enzyme activity of xylitol dehydrogenase in the recombinant S. cerevisiae was determined. The highest specific activity was 0.805 mU mg-1 protein or 0.013 nkat mg-1. This work demonstrates the functionality of the gene xylitol dehydrogenase from C. shehatae in S. cerevisiae.